Iacobi Monachi Epistulae. Edited by Elizabeth and Michael Jeffreys - Panagopoulos, Spyros (The journal of theological studies, 2011)
The collection of forty-three letters written by a monk to a sebastokratorissa Eirene is a compilation, of which only extracts have been edited. The author has collected and arranged texts borrowed mainly from the Christian writers of the fourth century (Basil of Caesarea, Gregory of Nazianzus, Greogory of Nyssa, John Chrysostom, Evagrius Ponticus) and secondarily from two commentators of the Scriptures (pseudo-Procopius of Gaza and Nicetas of Heraclea). Basil's correspondence provides the essential framework of literary letters. The monk Jacob intervenes only for a few transitions between passages he copied, often with simple hinges (as γον, διὰ τοτο, διό, διότι, λοιπόν), to conclude a passage (καὶ τατα μὲν οὕτως) or the whole letter (Τατα πρὸς τὴν βασιλείαν σου, Ἰάκωβος μοναχός: cf.